Design for adaptability and disassembly: towards zero construction waste in the Australian housing sector / Lisa Kuiri and Paola Leardini - Kuiri, Lisa; Leardini, Paola (2022)
The built environment is the biggest consumer of natural resources globally, with construction and demolition materials among the biggest sources of waste in developed countries. In Australia, the housing sector continues to use construction methods based on a 'take-make-waste' linear model, which is an unsustainable practice for using materials on a planet of finite natural resources and increasing population. New design and construction practices are being developed internationally to target the most sustainable options for handling materials and components at a building's end of life. A transformational design shift is needed to transition the Australian housing construction market to a Circular Economy (CE), keeping materials in use for longer. However, while theoretically sound, the implementation of circular design in construction remains limited internationally, and the transition has not started in Australia yet. Based on a narrative and integrative review approach, this paper argues that an effective transition to a CE in construction, through adaptable housing models, has the potential to eliminate material waste while addressing demographic changes of diverse Australian stakeholders. This paper questions the paradigm of one household on one lot in sprawled suburbs dominated by detached housing, and advocates for alternative housing models, such as incremental housing, to increase suburban density. Enabled by advances in prefabricated timber technology, design for disassembly may augment this approach, enabling housing designed for adaptability, to grow and contract in size in response to changing household needs and desires.